Aplicaciones de la tecnología de irradiación en el espárrago peruano - Vargas R, Johnny (2019)
irradiation technology replaces additives and chemical fumigants in the conservation and elimination of insects in food. These chemicals are very questionable to be highly toxic, harmful to health and the environment. We present research using gamma radiation in Peruvian asparagus (fresh asparagus, freeze-dried and flour). Doses of 1 kGy extend the half-life of fresh green asparagus for 20 days and of the control for only 10 days. The quality of freeze-dried asparagus irradiated to 3, 5 and 7 kGy was evaluated by microbiological, physicochemical and sensorial tests. a dose of 3 kGy improved the hygienic quality of freeze-dried asparagus. irradiation was evaluated as a quarantine treatment for the disinfestation of copitarsia decolora in asparagus. a dose of 0.10 kGy applied to the second instar of copitarsia decolora larvae was required to prevent adult emergence. Gamma radiation in Peruvian asparagus, extend half-life, improve the hygienic quality and as a quarantine treatment will be an alternative to methyl bromide fumigation, which affects the quality of the product, damages health and the environment.